Extensive penile skin necrosis after surgery for Peyronie's disease - M. E. Topuzov; O. V. Stetsik; S. M. Basok; P. V. Kustov; O. A. Abinov (Вестник урологии, 2021)
The clinical case represents the surgical correction of postoperative complications in a patient with Peyronie's disease. The patient underwent flap corporoplasty using an autovein. The late postoperative period in the patient was complicated by extensive necrosis of the penile skin, which required repeated surgery as follows. The first stage of surgical treatment was performed by excision of necrotic tissues of the penile skin. Within 10 days of the postoperative period, chymotrypsin with an ointment containing dioxomethyltetrahydropyrimidine with chloramphenicol was applied to the penile wound surface to prepare the wound for subsequent skin autotransplantation. Further, within 5 days, the polymeric drainage sorbent «Aseptisorb DT» was applied to the wound surface until the wound was cleansed and granulation tissue was formed. The second stage of the surgical treatment performed penile skin replacement plasty with a free perforated skin graft taken from the patient's femoral surface.